Factors related to left ventricular hypertrophy in adult persons living at altitude: Factores relacionados con hipertrofia ventricular izquierda en personas adultas que viven en altura - Diaz Lazo, Anibal Valentin (2020)
Objective: to determine the factors related to left ventricular hypertrophy (LVH) in adults living high. Methods: An observational, cross-sectional and analytical study was carried out in the Echocardiography Laboratory of the Hospital Regional Docente Clínico (HRDCQ) Daniel Alcides Carrión (HRDCQ) of Huancayo, Peru at 3,259 m.s.n.m. The sample was determined with a formula and the sampling was simple random. The inclusion criteria were: be 18 years of age or older; have an echocardiography study with a diagnosis of LVH. The exclusion criteria were: having valvular disease, congenital heart disease, dilated cardiomyopathy, acute cardiovascular event, and cardiac arrhythmia. The data were collected in a file. For the statistical analysis, the X2 test, student's t test, binary and multivariate logistic regression, odds ratio, 95% confidence interval were applied. P <0.050 was considered significant. Results: 488 patients were included, the average age was 64 years (range: 18-98). In 58.9% (370) they were women. The factors related to LVH were arterial hypertension (OR = 5.90; 95% CI = 3.57-9.75), age 60 years and older (OR = 3.13; 95% CI = 2.04-4 , 81), diabetes mellitus (OR = 2.92; 95% CI = 1.03-8.21), and obesity (OR = 2.25; 95% CI = 1.16-4.35) compared to patients without LVH. In patients with LVH, a higher left atrial volume index and left ventricular diastolic dysfunction were found. Conclusions: the factors related to LVH in adults living at height were arterial hypertension, advanced age, diabetes mellitus and obesity.